2021
DOI: 10.1111/scd.12671
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of oral health outcomes for people with cerebral palsy

Abstract: Introduction Good oral health is important for good overall health. Studies have reported poorer oral health outcomes for people with cerebral palsy, but there has been no synthesis of the evidence surrounding this and, there are no clear oral health recommendations for people with cerebral palsy globally. This review synthesizes the existing knowledge base on oral health in people with cerebral palsy and provides recommendations for future research. Methods A scoping review was conducted to assess the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…After applied proposed search strategy a total of 185 articles were found ranging from 1965 (Adelson, 1965) to 2021 (Lansdown et al, 2022-Epub 2021. Thus, there was no year restriction regarding inclusion in this study.…”
Section: Resultsmentioning
confidence: 99%
“…After applied proposed search strategy a total of 185 articles were found ranging from 1965 (Adelson, 1965) to 2021 (Lansdown et al, 2022-Epub 2021. Thus, there was no year restriction regarding inclusion in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have established that people with CP have poor oral health, including an increased prevalence of dental trauma, periodontal disease and a high prevalence of dental caries. 11 Similarly, studies conducted in Saudi Arabia have also suggested that people with CP have a higher prevalence of oral disease. 12,13 However, no systematic review has been published to date, to provide an overview of the research conducted on this topic, including no guidelines or a summary of the current state of oral health of individuals with CP in KSA.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the neonatal mortality rate and incidence of stillbirth have decreased significantly because of the development of medicine. However, the incidence of CP has not decreased, and the proportion of patients with severe CP has increased 5–7 . Approximately half of children with CP have disrupted upper extremity (UE) function, such as difficulty in reaching, grasping, or manipulating objects 8 .…”
mentioning
confidence: 99%
“…However, the incidence of CP has not decreased, and the proportion of patients with severe CP has increased. [5][6][7] Approximately half of children with CP have disrupted upper extremity (UE) function, such as difficulty in reaching, grasping, or manipulating objects. 8 More than 50% of children with CP have lower extremity (LE) movement disorders, which manifest as LE muscle contractures, ankle stiffness deformities, flexion of the hips and knees when standing and walking, etc.…”
mentioning
confidence: 99%